Practical bootcamp JWT authentication with Java and Spring Boot. (Packt Publishing, 2022)
Understand JWT authentication and authorization and use it to secure your Spring Boot-based microservices. About This Video Learn various components and terminology associated with JWT Extract user information and role information from JWT Create security-related classes such as configuration, filters, services In Detail JWT (JSON web token) is a standard for securing APIs in a Microservices architecture; using this standard, we can secure APIs' built-in technology such as Nodejs, Python, .NET, and so on. But in this course, we will build APIs using Java and Spring Boot and then we will be securing them using JWT and Spring security. We will cover important concepts such as authentication, authorization, the importance of securing RESTful APIs, JWT (Json Web Token), various components and terminology associated with JWT, Workflow, and a diagrammatic use case of using JWT. Along the course, you will learn to implement JWT in our Spring Boot project by creating a Spring Boot project from scratch. We will add the required Maven dependencies and learn to set up projects in GitHub and follow a continuous integration process. You will also learn to create our Hibernate entity classes and start configuring JWT and Spring security. Moving further, we will configure the allowed and not allowed endpoints and create user registration and login endpoints. We will understand how to create role-based classes and create multiple roles as well as restrict users to functionalities based on roles. By the end of the course, you will learn to create security-related classes such as configuration, filters, and services, and learn to use Postman to test our APIs. Audience This course is for anyone who wants to learn about securing APIs at an industry-grade standard.